Actuarial implications and modeling of virus yellows on sugar beet after the EU's ban on neonics and climate change - Martial Phélippé-Guinvarc'h; Jean Cordier (Smart Agricultural Technology, 2024)
Following the EU's decision to ban neonics, this article investigates the impacts of virus yellows on sugar beet yields under the ban and under current and future climates. Using a model that factors in key variables such as sowing dates, phenological stages, first aphid flight and aphid abundance, simulations are performed using long-period climate datasets as inputs. Coupled with incidence and sugar yield loss assumptions, this model allows to reconstruct the impact of virus yellows on sugar beet yields using a so called ‘as if’ approach. By simulating the effects of viruses over a long period-of-time, as if neonics weren't used in the past, this methodology allows an accurate assessment of risks associated with virus yellows, as well as impact of future agro-ecological measures.The analysis provides in addition an actuarial rating for an insurance policy that compensates the losses triggered by those viruses.